Comparison of the Effect of Glycemic Control in Type 2 Diabetes Outpatients Treated With Premixed and Basal Insulin Monotherapy in China - Liu, Guangxu; Dou, Jingtao; Pan, Yuesong; Yan, Yuxiang; Zhu, Huiping; Lu, Juming; Gaisano, Herbert; Ji, Linong; He, Yan (Frontiers in Endocrinology, 2018)
Background: Basal and premixed insulin have been widely used for insulin therapy of type 2 diabetes mellitus (T2DM) in China. The aim of this study is to compare the sustained efficacy of basal and premixed insulin therapies in T2DM outpatients with insulin monotherapy. Materials and Methods: The survey was conducted in 602 hospitals across China from April to June in 2013. The participants included outpatients who were receiving basal or premixed insulin monotherapy for more than 3 months, and the outcome was attaining a glycated hemoglobin A1C (HbA1c) of <7.0% as a measure of sustained glycemic control. Results: A total of 49,119 T2DM outpatients on basal (n = 11,967) or premixed insulin (n = 37,152) monotherapy were included in the final analyses. Using multivariable model analysis, patients using premixed insulin exhibited a better glycemic control, with more outpatients achieving the target HbA1c level than those using basal insulin (model 1, OR 0.695, 95%CI 0.664–0.728; model 2, OR 0.708, 95%CI 0.676–0.742; model 3, OR 0.717, 95%CI 0.684–0.752; model 4, OR 0.750, 95%CI 0.715–0.787). Using subgroup analysis stratified by age, sex, duration of diabetes, duration of insulin treatment, and complications, still more outpatients in every subgroup treated with premixed insulin achieved the target HbA1c (HbA1c < 7%) than those receiving basal insulin. Conclusions: Premixed insulin monotherapy had a better glycemic control (HbA1c < 7.0%) than basal insulin monotherapy for Chinese T2DM outpatients in daily.